2015
DOI: 10.4236/as.2015.65055
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Gated Pipes Technique for Improving Surface Irrigation Efficiency in Maize Hybrids

Abstract: Waterlogging and low application efficiency are the main problems inherent with surface irrigation in the Nile Delta. Develop surface irrigation using gated pipes (GP) is a new method to be used to distribute water into furrow irrigated fields as strategy based on water saving. Laboratory calibration was conducted out to evaluate the hydraulic characteristics of pipe gates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
(33 reference statements)
4
7
0
Order By: Relevance
“…[7] found that WUE can be improved by 12-29% when using well designed gated pipes instead of traditional surface irrigation for the cultivation of cotton and wheat, under Egyptian conditions. Similar results were achieved considering yield and water application for the cultivation of five different varieties of corn under gated and traditional irrigation systems [10][11][12] compared yields of cotton, wheat, corn, and rice under gated pipes and flooding irrigation and indicated that the yields of these crops were higher under gated pipes by 61.1, 65.2, 116 and 53.6 %, respectively, while significant water savings were achieved (29.64, 29.9, 14.5 and 19.7 %, respectively). [13] found that using gated pipes could raise sugar cane productivity by 11.8 -16% while saving 32.3-35.6% of water, decreasing the irrigation time by 37-38%, and rising the total irrigation efficiency to 75% compared to conventional systems (flood irrigation and planting in furrow) for El-Minia, Luxor and Aswan regions.…”
Section: Introductionsupporting
confidence: 74%
“…[7] found that WUE can be improved by 12-29% when using well designed gated pipes instead of traditional surface irrigation for the cultivation of cotton and wheat, under Egyptian conditions. Similar results were achieved considering yield and water application for the cultivation of five different varieties of corn under gated and traditional irrigation systems [10][11][12] compared yields of cotton, wheat, corn, and rice under gated pipes and flooding irrigation and indicated that the yields of these crops were higher under gated pipes by 61.1, 65.2, 116 and 53.6 %, respectively, while significant water savings were achieved (29.64, 29.9, 14.5 and 19.7 %, respectively). [13] found that using gated pipes could raise sugar cane productivity by 11.8 -16% while saving 32.3-35.6% of water, decreasing the irrigation time by 37-38%, and rising the total irrigation efficiency to 75% compared to conventional systems (flood irrigation and planting in furrow) for El-Minia, Luxor and Aswan regions.…”
Section: Introductionsupporting
confidence: 74%
“…The field experiments done in clay soil. The soil properties tabulated in table (3) according to Jackson (1967) and (Ali and Mohammed, 2015). The performance of the two hydrants can determine by the following guides: Water infiltration: The "Zf" was measured in the upper of 30 cm above soil surface using double ring infiltrate-meter at beginning of experiment at the site location according to Micheal (1978).…”
Section: Methodsmentioning
confidence: 99%
“…Egypt presents a typical example of the drought problem faced in some arid districts (Hammad & Ali, 2014). Irrigation is one of the most important factors in affecting crop productivity as well as water and fertilization use efficiency (Mehanna et al, 2013;Ali & Mohammed, 2015). In Egypt, limited water resources are the main factor facing expansion of wheat growing areas.…”
Section: Introductionmentioning
confidence: 99%